Actuality of the Chomsky-Skinner controversy (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
The objective of this work is to reassess the Chomsky-Skinner controversy, 50 years after the publication of Verbal Behavior. For this purpose, I will summarize some of the hypotheses proposed by Skinner (1), then I will analyze the criticisms by Chomsky (2), and will expose some of the most recent answers to the argument that the complexity of language and the poverty of stimulus imply an innate knowledge of grammar (3). It is concluded that the attitude of opposition towards Skinner’s theses by many language researchers was originated largely due to mistakes in Chomsky’s criticisms, that the Chomsky-Skinner controversy is not closed, and that the proposals of Verbal Behavior are still implemented in diverse research programs.